Clinical and pathological analyses of 73 cases of lichen sclerosus in females - Qing-na GENG; Xu-hui FU; Dan-dan WU; Lei-sheng REN; Zhe-xin WANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2020)
Objective: To analyze the clinical and histopathological characteristics of lichen sclerosus in 73 female patients. Methods: The diagnosis and the treatment of lichen sclerosus were retrospectively analyzed in 73 female patients, who were treated in our department. Results: Out of 73 patients, 46.58% were over 50 years old, and 38.36% were between 14 and 50 years old. The rest (15.07%) were under 14 years old. Skin lesions often involved the vulva. The basic pathological changes included hyperkeratosis, vacuolar degeneration of basal layer, superficial dermal edema, hyaline degeneration of collagen homogenization, as well as various degree of infiltration of lymphocytes and histiocytes. Conclusions: The diagnosis of lichen sclerosus can be made according to its clinical and histopathological features. The treatment should be based on the histopathological changes. Medical professionals should be familiar with early stage of lichen sclerosus in order to reduce misdiagnosis. Appropriate treatment regimen can be chosen according to the stage of the disease.